Percursos de leitura : trabalhando com a letra de canção na sala de aula - Souza, Eliana Aparecida Albergoni de (2014)
This paper reflects on the discursive genre "Song lyrics" and proposes its use in Portuguese Language classes in order to contribute to the formation of critical and independent readers, as recommended by the Curricular Guidelines for High School (OCEM). The reflections and analysis were anchored in the enunciative-discursive theory of socio-historical approach of BAKHTIN ([1929] 2004) and the Circle. To situate the genre Song lyrics within Bakhtinian theory, as a poetic genre of discourse, we started from the concepts of Padilha (2005). Low levels of reading performance of Brazilian students in evaluative events like Prova Brasil and PISA indicate the need to reevaluate the teaching of reading and the importance of proposals involving new approaches for the texts that are brought into the classrooms. The proposals presented in this dissertation attempt to meet these needs and are organized according to the guidelines of OCEM on reading. The work here suggested of analysis of song lyrics in the classroom, trying to visualize the structure, the ideological traces, the conditions of production and the communicative intention in the text, was designated as pathways in reading.